2000
DOI: 10.1034/j.1600-0722.2000.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypothalamic‐pituitary‐adrenal axis reactivity on periodontal tissue destruction in rats

Abstract: The aim of this study was to test the hypothesis of an association between hypothalamic-pituitary-adrenal (HPA) axis reactivity and progression of periodontal disease. Histocompatible Lewis and Fischer 344 rats respond to stressful stimuli with low and high HPA axis reactivity, respectively. Experimental periodontitis was induced by tying a silk ligature around the neck of maxillary 2nd right molar teeth in 10 Lewis and 10 Fischer 344 rats with contralateral non-manipulated teeth as controls. Twenty non-manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(127 citation statements)
references
References 24 publications
6
115
0
6
Order By: Relevance
“…In addition, observational studies in humans have pointed out this same relationship, but with poor information regarding biological events 7 . Despite this, we still lack the establishment of stress as a risk factor 14 as occurs, for instance, to diabetes and tobacco At the present time, there are a reasonable number of studies demonstrating that manipulation of the HPA axis can either lead to greater progression of periodontitis 16 or prevent its progression 17 . In this sense, other evidences have indicated that this manipulation could start, perhaps in the near future, even before birth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, observational studies in humans have pointed out this same relationship, but with poor information regarding biological events 7 . Despite this, we still lack the establishment of stress as a risk factor 14 as occurs, for instance, to diabetes and tobacco At the present time, there are a reasonable number of studies demonstrating that manipulation of the HPA axis can either lead to greater progression of periodontitis 16 or prevent its progression 17 . In this sense, other evidences have indicated that this manipulation could start, perhaps in the near future, even before birth.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, adrenal hyperactivation has been found to increase infection susceptibility 9 and increase the risk for development of periodontal disease. 10 Periodontal disease is related to loss of teeth. 11 Accelerated tooth eruption has been reported in patients with CAH.…”
Section: Congenital Adrenal Hyperplasia (Cah)mentioning
confidence: 99%
“…Many kinds of animals have been used for periodontitis research previously, non-human primates 1,2) , dogs 3,4) , rats 5,6) , mice 7,8) and so on 9) ; however, each of these animals has particular characteristics. For example, in non-human primates and dogs, the progress of periodontitis is similar to that in humans; however, they are difficult to handle and are expensive 10) .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the use of non-human primates has ethical issues 10) . On the other hand, although rodents including rats and mice are resistant to periodontitis naturally, they are used for periodontal research [3][4][5][6] , since they are easy to handle and are inexpensive 10) . In rats and mice, experimental periodontitis is induced by inoculation of bacteria [6][7][8][11][12][13] and placement of ligatures 5,[14][15][16][17] ; however, for inoculation of bacteria, the experiment includes bacteria culture, the method of inoculating bacteria is complicated, and a long period is required to establish periodontitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation